Fasudil in Combination With Bone Marrow Stromal Cells (BMSCs) Attenuates Alzheimer’s Disease-Related Changes Through the Regulation of the Peripheral Immune System - Yu, Jiezhong; Yan, Yuqing; Gu, Qingfang; Kumar, Gajendra; Yu, Hongqiang; Zhao, Yijin; Liu, Chunyun; Gao, Ye; Chai, Zhi; Chumber, Jasleen; Xiao, Bao-Guo; Zhang, Guang-Xian; et al. (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a chronic progressive neurodegenerative disease. Its mechanism is still not clear. Majority of research focused on the central nervous system (CNS) changes, while few studies emphasize on peripheral immune system modulation. Our study aimed to investigate the regulation of the peripheral immune system and its relationship to the severity of the disease after treatment in an AD model of APPswe/PSEN1dE9 transgenic (APP/PS1 Tg) mice. APP/PS1 Tg mice (8 months old) were treated with the ROCK-II inhibitor 1-(5-isoquinolinesulfonyl)-homo-piperazine (Fasudil) (intraperitoneal (i.p.) injections, 25 mg/kg/day), bone marrow stromal cells (BMSCs; caudal vein injections, 1 × 106 BMSCs /time/mouse), Fasudil combined with BMSCs, or saline (i.p., control) for 2 months. Morris water maze (MWM) test was used to evaluate learning and memory. The mononuclear cells (MNCs) of spleens of APP/PS1 Tg mice were analyzed using flow cytometry for CD4+ T-cells, macrophages, and the pro-inflammatory and anti-inflammatory molecules of the macrophages. Immunohistochemical staining was used to examine the expression of ROCK-II in the spleens of APP/PS1 Tg mice. The MWM test showed improved spatial learning ability in APP/PS1 Tg mice treated with Fasudil or BMSCs alone or in combination, compared to untreated APP/PS1 Tg mice. Fasudil combined with BMSCs intervention significantly promoted the proliferation of CD4+/CD25+ and CD4+/ IL-10 lymphocytes, induced the release of cytokine factors, and regulated the balance of the immune system to work functionally. It also shifted M1 (MHC-II, CD86) to M2 (IL-10, CD206) phenotype of macrophages of CD11b and significantly enhanced the anti-inflammatory and phagocytic abilities (CD16/32) of macrophages of CD11b. Immunohistochemical staining showed significantly decreased expression of ROCK-II in mice treated with combination of Fasudil with BMSCs as compared to saline control. Fasudil in combination of BMSCs improved cognition of APP/PS1 Tg mice through the regulation of the peripheral immune system, including reduction of ROCK-II expression and increased proportion of anti-inflammatory M2 mononuclear phenotype and phagocytic macrophages in the spleen of the peripheral immune system. The latter was achieved through the communication between brain and spleen to improve the immunoregulation of CNS and AD disease conditions.